Essencism as an African Paradigm Towards the Salvation of the Environment - Ekanem, Samuel Asuquo; Aboh, Magdalyn; Oweh, Kidzu T. (European Journal of Sustainable Development, 2017)
The present global environmental crisis is traceable to certain fundamental strands of Judeo-Christian thinking that actually encourage the over exploitation of nature for the sole benefit of man. This is anchored on the firm belief that nature as created is basically for the purpose of manhumans. This Judeo-Christian thinking of man’s dominance of the earth is classically depicted or captured in Genesis Chapter 1, Verse 27-28 where the Bible says “God created man in his own image, in the image of God created He him, male and female created He them. And God blessed them, and God said unto them, be fruitful and multiply and replenish the earth, and subdue it: and have dominion over fish of the sea and over fowl of the air, and over every living thing that moveth upon the earth”. This biblical command and blessing constitute what emboldened the human race to see nature as an object of exploitation and exploration. This also, promote isolationism of humansman as being distinct and different from nature. With this isolationist understanding and posture, man developed his twin cognitive activities of science and technology as portent instruments of exploitation and exploration to conquer nature. It is therefore the development of science and technology as both instrument of exploitation, exploration and weapon to conquer and subdue nature that has led to several dislocation of nature’s delicate balance, which has brought what is generally refer to as environmental problems or crisis. In this paper therefore, effort will be made to show that it is the activities of man through the instrumentality of science and technology that has created the environmental hazards that the world is now faced with. It will also be argued the extremism necessitated by the Judeo-Christian thinking can be moderated through the educative process, which can be achieved through essencism as a philosophy. It is the position of the paper that the current environmental crisis can be curbed through a process that will make man to realize his essence on earth. Keywords: Essencism, Africa, Paradigm, Salvation and Environment